Key genes and pathways involved in the pathogenesis of pemphigus foliaceus: Based on bioinformatic studies - Yaqian ZHU; Xinhui LI; Ziyue JIA; Yongfeng CHEN (Pifu-xingbing zhenliaoxue zazhi, 2023)
Objective Using bioinformatic technique to identify key genes and pathways involved in the pathogenesis of pemphigus foliaceus (PF), in order to elucidate the pathogenesis of PF. Methods Gene microarray dataset GSE53873 of peripheral blood CD4+ T cells from PF patients was obtained from Gene Expression Omnibus database, and various bioinformatics methods such as Limma difference analysis, gene function and pathway enrichment analysis, and protein-protein interaction network analysis were integrated to determine the key genes and pathways associated with PF. Results A total of 121 significantly upregulated genes and 48 significantly downregulated genes were identified in PF patients compared with healthy controls. The differentially expressed genes in PF patients were involved in multiple functions such as T cell differentiation, T cell activation, leukocyte differentiation and metabolism. CXCL10 and OAS1 were identified as key genes in the pathogenesis of PF. Receiver operating characteristic (ROC) results suggested that CXCL10 (AUC=0.86) and OAS1 (AUC=0.86) had high diagnostic efficacy for PF. Gene function and pathway enrichment analysis indicated that CXCL10 was mainly associated with TOLL-like receptor signaling pathway, COVID-19 infection, and cytokine interaction, while OSA1 was mainly associated with viral infection and type I interferon signaling pathway. Conclusions CXCL10 and OAS1 are the key genes associated with PF. The pathogenesis of pemphigus is associated with pathways such as T cell differentiation and activation, leukocyte differentiation and metabolism.